Implementation of School-Based Management to Improve the Quality of Education at SMA Negeri 1 Woha - Radeshak, Ridha Rangga; Umar, Umar; Subari, Subari (JUPE : Jurnal Pendidikan Mandala, 2024)
This research is a descriptive qualitative research with data collection techniques through observation, interviews, and documentation. The purpose of this study is to provide an overview of the implementation of School-Based Management (SBM) at SMA Negeri 1 Woha, in an effort to improve the quality of education. The findings of the study show that SMA Negeri 1 Woha has been independent enough to meet the availability of teachers and other support staff, as well as sufficient and adequate in terms of the availability of facilities and infrastructure. Strong school collaboration, as evidenced by the direction, and internal relationships built with MGMP within the school. In addition, there is an MoU built with other partnerships to collaborate in the progress of the school. As well as the existence of physical support, and human resources from stakeholders for the implementation of education at SMA Negeri 1 Woha. Another thing is that SMA Negeri 1 Woha has the openness of the school to disseminate information through meeting activities and school bulletin boards, which is an indication of good school transparency. And school accountability is seen from the process of financial responsibility carried out through the preparation of school accountability reports. Meanwhile, the obstacles and obstacles faced by SMA Negeri 1 Woha include several obstacles to the implementation of school-based management, namely: Lack of financial resources; Lack of human resources; Facilities and infrastructure; Lack of community support to support the implementation of school-based management (SBM).